Analisa Kekasaran Permukaan Dari Metode Pemotongan Tangensial Pada Proses Pemesinan Turn-Milling - Muhammad Iqbal; Yohanes Yohanes; Anita Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The surface roughness of a machining process is a very important factor in the field of production that is one of the turn-milling process. Turn-milling is a combined machining process of turning and milling with complete tools (cutting) where workpieces and tools rotate together. The turn-milling process can be classified in orthogonal turn-milling, tangential turn-milling and co-axial turn-milling. The resulting surface surface quality is also affected by the parameters of the machining process in the form of rotation of the workpiece and the rotation of the tool. The purpose of this research is to know the effect of parameters on surface roughness and optimal Parameter to surface roughness by doing tangential process of turn-milling. By varying the parameter variables, the surface roughness generated in this study is influenced by the rotation of the workpiece and the rotation of the tool. The higher the tool rotation the lower the surface roughness. As well as the rotation of the workpiece the higher the rotation of the workpiece the finer the surface results. The optimal parameter is a rotation tool -2500 rpm with a rotation of 1000 rpm objects found in the roughness class N6 with a roughness value of 1.282 μm where the roughness value is lower than the other roughness values.Keywords: Turn-Milling, Tangential Turn-Milling, Rotation, Surface Roughnees